The Impact of Contextual Teaching and Learning on Students’ Cognitive Abilities in Material of My Region My Pride - Br Sembiring, Adelina; Yusnaldi, Eka (Yayasan Sembilan Pemuda Indonesia, 2025)
This study aims to investigate the impact of the Contextual Teaching and Learning (CTL) model on the cognitive abilities of fifth-grade students in learning the topic “My Region, My Pride” at MIS Maura El-Mumtaz, Binjai City. The research seeks to determine whether CTL, which connects learning material to real-life experiences, enhances students’ understanding compared to conventional methods. A quasi-experimental design with a non-equivalent control group was employed. The sample consisted of 40 students divided into an experimental group (taught using CTL) and a control group (taught without CTL). Data were collected through pretests and posttests, and statistical analysis, including N-Gain scores, was used to measure learning improvement. The findings revealed a significant difference in posttest scores between the experimental and control groups (*p* < 0.05), with the CTL group achieving a higher average score (89.95) compared to the control group (75.65). The N-Gain analysis further confirmed greater improvement in the experimental class (82.70) than in the control class (57.16). This study contributes to existing literature by empirically validating the effectiveness of CTL in enhancing cognitive abilities in social studies, particularly in local wisdom-based learning an area that has received limited attention in prior research. The results suggest that educators should consider adopting CTL strategies to make learning more meaningful and engaging, particularly in subjects requiring contextual understanding, such as social studies. This research provides evidence supporting CTL as an effective pedagogical approach, offering insights for curriculum developers and teachers aiming to improve student learning outcomes through experiential and context-based instruction.